Draft Fifth Five Year Plan (1974-79) Part II—Statements Union Territory of Delhi - Planning Commission (Planning Commission, 1974)
Land for setting up of flatted factories at three sets will be acquired. Land for setting up of Electronic complex will be acquired. Half of construction work at Flatted factories for Electronics and plastics and leather goods will be completed during 1974-75.
Union Territory of Delhi, Planning Department